The Role of English Movies in Modern Enhancing Listening Skills - Putri, Ni Made Dwi Ratih Pramita (English Language and Education Spectrum, 2025)
This study explores the role of English-language movies in improving listening skills among English as a Foreign Language (EFL) learners from various backgrounds. Using a quantitative descriptive approach, data were collected from 30 participants through an online questionnaire. The instrument examined participants’ movie-watching habits and their perceptions of how English movies support listening development. The findings show that most respondents frequently watch English movies for both learning and entertainment purposes, with YouTube and Telegram being the most preferred platforms. Disney and drama genres were highly favored due to their clear pronunciation and engaging storylines. English subtitles were widely used to support understanding of spoken content. The results indicate that English movies are perceived as highly beneficial in enhancing listening comprehension, pronunciation, and vocabulary acquisition. Additionally, participants reported increased confidence and motivation when learning through movies compared to traditional methods. Descriptive statistical analysis revealed strong positive trends in learner attitudes, especially in relation to enjoyment and vocabulary gain. The study concludes that English movies, when used intentionally and supported by subtitles, serve as an effective tool for developing listening skills across diverse learner groups and can complement formal or independent language learning practices.